Development of the Concept of a Collection of Dresses from Khonatlas Fabric - Mavjudaxon Ulug‘boboyeva (Genius Journals, 2022)
In the problems of modern design, the problem of creative concept (the main idea, the merits and tasks of design, the spiritual path) occupies a central place. Conceptuality is a general creative instruction that underpins the essence of a project culture. This article is about the development of the concept of a collection of dresses made of khan satin fabric.
Keywords: Conceptuality; wardrobe; elegant flowers